Prospective association between added sugars and frailty in older adults. Issue 5 (9th April 2018) - Laclaustra, Martin; Rodriguez-Artalejo, Fernando; Guallar-Castillon, Pilar; Banegas, Jose R; Graciani, Auxiliadora; Garcia-Esquinas, Esther; Ordovas, Jose; Lopez-Garcia, Esther
ABSTRACT: Background: Sugar-sweetened beverages and added sugars (monosaccharides and disaccharides) in the diet are associated with obesity, diabetes, and cardiovascular disease, which are all risk factors for decline in physical function among older adults. Objective: The aim of this study was to examine the association between added sugars in the diet and incidence of frailty in older people. Design: Data were taken from 1973 Spanish adults ≥60 y old from the Seniors-ENRICA cohort. In 2008–2010 (baseline), consumption of added sugars (including those in fruit juices) was obtained using a validated diet history. Study participants were followed up until 2012–2013 to assess frailty based on Fried's criteria. Statistical analyses were performed with logistic regression adjusted for age, sex, education, smoking status, body mass index, energy intake, self-reported comorbidities, Mediterranean Diet Adherence Score (excluding sweetened drinks and pastries), TV watching time, and leisure-time physical activity. Results: Compared with participants consuming <15 g/d added sugars (lowest tertile), those consuming ≥36 g/d (highest tertile) were more likely to develop frailty (OR: 2.27; 95% CI: 1.34, 3.90; P -trend = 0.003). The frailty components "low physical activity" and "unintentional weight loss" increased dose dependently with added sugars. Association with frailty was strongest for sugars added during food production. Intake of sugars naturally appearing in foods was not associated with frailty. Conclusions: The consumption of added sugars in the diet of older people was associated with frailty, mainly when present in processed foods. The frailty components that were most closely associated with added sugars were low level of physical activity and unintentional weight loss. Future research should determine whether there is a causal relation between added sugars and frailty.